High Quality Machine Translation Using A Machine-Learned Sentence Realization Component - Smets, Martine; Gamon, Michael; Pinkham, Jessie; Reutter, Tom; Pettanaro, Martine (Association for Machine Translation in the Americas, 2003)
We describe the implementation of two new language pairs (English-French and English-German) which use machine-learned sentence realization components instead of hand-written generation components. The resulting systems are evaluated by human evaluators, and in the technical domain, are equal to the quality of highly respected commercial systems. We comment on the difficulties that are encountered when using machine-learned sentence realization in the context of MT.